With Gratitude from RHiME: Reviewers 2025 - RHiME, Editor (Research and Humanities in Medical Education, 2026)
The Editorial Board of RHiME would like to thank the following reviewers for their outstanding contributions to the work of the journal. Without their dedication and the time they devoted to the evaluation of submissions made to RHiME, it would have been impossible to maintain the standard of the journal. Anand Zachariah Ann Helen Prasad Anuradha Joshi Chetna Dengri Hara Prasad Mishra Harikeerthan Raghuram Harsh Sharma Harshal Sabane Munira Hirkani Navjeevan Singh Neha Joe Pooja Priyamvada Prabhakar AT Pranab Chatterjee Prateek Suresh Harne Prema Saldanha Prithviraj Bose Rajat Thawani Reena George Sadhika Sood Satendra Singh Shruthi Ravishankar Sualeha Shekhani Varsha Shridhar Venkata Venu Gopala Raju Srijampana